Long-term monitoring of molecular markers can distinguish different seasonal patterns of fecal indicating bacteria sources. (15th March 2015) - Riedel, Timothy E.; Thulsiraj, Vanessa; Zimmer-Faust, Amity G.; Dagit, Rosi; Krug, Jenna; Hanley, Kaitlyn T.; Adamek, Krista; Ebentier, Darcy L.; Torres, Robert; Cobian, Uriel; Peterson, Sophie; Jay, Jennifer A.
Abstract: Elevated levels of fecal indicator bacteria (FIB) have been observed at Topanga Beach, CA, USA. To identify the FIB sources, a microbial source tracking study using a dog-, a gull- and two human-associated molecular markers was conducted at 10 sites over 21 months. Historical data suggest that episodic discharge from the lagoon at the mouth of Topanga Creek is the main source of bacteria to the beach. A decline in creek FIB/markers downstream from upper watershed development and a sharp increase in FIB/markers at the lagoon sites suggest sources are local to the lagoon. At the lagoon and beach, human markers are detected sporadically, dog marker peaks in abundance mid-winter, and gull marker is chronically elevated. Varied seasonal patterns of FIB and source markers were identified showing the importance of applying a suite of markers over long-term spatial and temporal sampling to identify a complex combination of sources of contamination. Highlights: Topanga Beach has well documented elevated levels of FIB. Historical FIB and flow data suggest discharge from the lagoon is key factor. FIB/markers from upper watershed development decline downstream. Lower watershed: human is sporadic, dog peaks mid-winter, gull is chronically high. MST shows varied seasonal marker patterns suggesting a combination of FIB sources.